Marketing Communication Strategy In Promoting The Train Ticket Discount Program During The Eid Season In 2025 (Study on Passenger Transportation Marketing and Customer Care Unit PT Kereta Api Indonesia Persero Divre III Palembang) - Luthfiah Sylmi Nadhirah; Sepriadi Saputra; M. Arif Setiawan (Universitas Muhammadiyah Palu, 2026)
Marketing communication strategies play an important role in increasing customer interest and loyalty, especially at the moment of Eid which is synonymous with high public mobility. PT Kereta Api Indonesia (Persero) Divre III Palembang through the Passenger Transportation and Customer Care Marketing Unit implements a marketing communication strategy to promote the 2025 Eid ticket discount program. This study aims to analyze how the strategy is designed and implemented in order to attract public attention and increase the number of passengers. The research method used is qualitative descriptive with data collection techniques through in-depth interviews, observations, and documentation. The results of the study show that marketing communication strategies include the stages of message planning, target audience determination, media selection, and evaluation of promotional effectiveness. PT KAI optimizes various communication channels such as social media, official websites, the Access by KAI application, as well as collaborations with online travel agents to expand the reach of information. The application of the Integrated Marketing Communication (IMC) theory can be seen from the integration between channels that produce consistent messages and strengthen the company's positive image. This strategy has proven effective with an increase in the number of Eid 2025 passengers to 99,039 people with an occupancy rate of 150%, an increase of about 20% from the previous year. Overall, an integrated and adaptive marketing communication strategy has succeeded in increasing the effectiveness of promotions and strengthening customer loyalty to PT KAI Divre III Palembang's services.